2016
DOI: 10.1016/j.susc.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Water co-catalyzed selective dehydrogenation of methanol to formaldehyde and hydrogen

Abstract: The non oxidative dehydrogenation of methanol to formaldehyde is considered a promising method to produce formaldehyde and clean hydrogen gas. Although Cu-based catalysts have excellent catalytic activity in the oxidative dehydrogenation of methanol, metallic Cu is commonly believed to be unreactive for the dehydrogenation of methanol in the absence of oxygen adatoms or oxidized copper. Herein we show that metallic Cu can catalyze the dehydrogenation of methanol in the absence of oxygen adatoms by using water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 57 publications
4
58
0
Order By: Relevance
“…In several cases it has been shown that by doping the coinage metals with PGMs at very low molar fractions, such that these more reactive metals disperse as isolated single atoms in the surface layer of the host material, the activity of the coinage metal surface can be dramatically enhanced whilst retaining excellent reaction selectivity [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. These single atom alloys (SAAs) of Sykes and co-workers exhibit tolerance to CO [18] and have been employed to catalyse hydrogenation [16][17][18][19][20], dehydrogenation [22,23], C-H activation and hydrosilylation [25] reactions with high activity and selectivity, as extended model surfaces and/or as real catalyst nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several cases it has been shown that by doping the coinage metals with PGMs at very low molar fractions, such that these more reactive metals disperse as isolated single atoms in the surface layer of the host material, the activity of the coinage metal surface can be dramatically enhanced whilst retaining excellent reaction selectivity [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. These single atom alloys (SAAs) of Sykes and co-workers exhibit tolerance to CO [18] and have been employed to catalyse hydrogenation [16][17][18][19][20], dehydrogenation [22,23], C-H activation and hydrosilylation [25] reactions with high activity and selectivity, as extended model surfaces and/or as real catalyst nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…These single atom alloys (SAAs) of Sykes and co-workers exhibit tolerance to CO [18] and have been employed to catalyse hydrogenation [16][17][18][19][20], dehydrogenation [22,23], C-H activation and hydrosilylation [25] reactions with high activity and selectivity, as extended model surfaces and/or as real catalyst nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Knowing the reaction kinetics can provide an insight into the system as it moves towards equilibrium. It is essential for testing hypotheses, for understanding reaction mechanisms, and for designing and optimizing chemical processes . Yet despite its importance, the task itself is often mundane, time‐consuming, and labour‐intensive.…”
Section: Figurementioning
confidence: 99%
“…It is essential for testing hypotheses,for understanding reaction mechanisms,a nd for designing and optimizing chemical processes. [1][2][3] Yetd espite its importance,t he task itself is often mundane,time-consuming,and labour-intensive.This is especially true when determining the temperature-dependence of rate constants,which requires multiple sets of various measurements.W hen dealing with reactions that produce gaseous products,t he quantification of gas production at the bench is ah assle.T his can be solved using on-line gas chromatography (GC) or mass spectrometry (MS). But since these instruments are expensive,and require long calibration procedures,the most commonly used method today is still the trusted upside-down glass burette.…”
mentioning
confidence: 99%
“…Performing chemical processes using metal catalysts has been considered due to the less cost of operational design in industrial sizes; due to the fact that they are in more suitable conditions in terms of temperature and pressure. Nowadays, a wide range of chemical materials are produced by catalytic conversion process for industrial purposes [9][10][11][12][13][14][15]. Several methods have been proposed for production of formaldehyde by oxidation of hydrocarbon gases, that is to say that, increasing formaldehyde levels is also done by these processes.…”
Section: Introductionmentioning
confidence: 99%